A Study of Solar Desalination Still Combined with Air-Conditioning System. (31st May 2012) - Abdel-Rehim, Z. S.; Lashine, A.
Abstract : A study of solar desalination still combined with air-conditioning system is presented in this work. Combining the solar still with the air-conditioning system can increase the condensate output from the solar still while meeting the cooling load needs. The operation of the combined solar distillation and air-conditioning system, that utilized the heat rejected by the condenser and the heat sink of the evaporator, has been tested to obtain the distillate output from the solar still during the air-conditioning of a space application. Experimental work of the present system is carried out in June 2009 (summer month), in Cairo, Egypt. The present problem is tested to use the integrated system operation for already utilizing air-conditioning energy consumption; that is, meeting the hourly air-conditioning load and the daily fresh water production. The system is tested for day and nighttimes of operation of the combined system for the summer month: June 2009, Cairo, Egypt. Economic study evaluation is presented. The results show that the maximum fresh water productivity through June is 29 Liters in daytime of June 5 2009 and 37 liters in nighttime (nocturnal time) of June 3 2009. The present system more efficient in day time (8:00 AM–8:00 PM) and night time (8:00 PM–8:00 AM). Therefore, the maximum efficiency is recorded 40% for the present system in daytime, 36% in nighttime, and 25% for conventional solar still. COP increases with inside temperature (T i ), however it decreases with outside temperature (T amb ). The average cost of one liter of distillate water from the present combined system = 0.021441 (LE).